2022
DOI: 10.29303/jppipa.v8i3.1673
|View full text |Cite
|
Sign up to set email alerts
|

Application of Immersive Virtual Learning to Understanding Climate Change Concepts and Thinking Process Skills

Abstract: problem of climate change is currently a problem that worries people around the world. Education is considered one way to solve this problem. However, the material on climate change is challenging to understand because the concepts contained in it are complex and require good thinking skills. Therefore, learning is needed that can facilitate this. Immersive Virtual Learning (IVL) analyzes the results of its application to students' understanding and thinking process abilities. The use of a pre-post control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…It was further revealed that environmental education had an effect on students' knowledge of the environment. Similar to what was said by Al Mufida et al (2022) that learning based on something real can have a positive effect on student knowledge. Knowledge of conservation related to living things can also be taught through environment-based learning (Schelly et al, 2012).…”
Section: Significantly Differentsupporting
confidence: 73%
“…It was further revealed that environmental education had an effect on students' knowledge of the environment. Similar to what was said by Al Mufida et al (2022) that learning based on something real can have a positive effect on student knowledge. Knowledge of conservation related to living things can also be taught through environment-based learning (Schelly et al, 2012).…”
Section: Significantly Differentsupporting
confidence: 73%